COMPARATIVE PHYTOCHEMICAL PROFILE AND ANTIOXIDANT PROPERTY OF BARK, FLOWERS AND LEAVES EXTRACTS OF SIMAROUBA GLAUCA - SAJEEDA N; KOLGI RR; SHIVAKUMARA SL; SHIVARAJ Y; KARIGAR CS (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The current study was to evaluate and compare the phytochemical constituents and antioxidant activity of bark, flowers and leaves of the tree Simarouba glauca. Methods: The solvent extraction of phytochemicals was carried out using Soxhlet apparatus with ethanol, chloroform, methanol, and water. The antioxidant property was determined by 2,2-Diphenyl-1-picrylhydrazyl, hydrogen peroxide free radical scavenging, reducing power assay, and nitric oxide radical scavenging assay using gallic acid and ascorbic acid as the standards. Results: The extraction yield was found maximum in the water extract of flower (3.7% w/w). Qualitative and quantitative analysis of phytoconstituents showed that the highest amount of alkaloids and flavonoid content (2.1% w/w) and (3.9% w/w), respectively, was in the chloroform extract of the flower. Phenol and carbohydrate constituent was found to be highest in the methanol extract of leaves 2.5% w/w and 2.2% w/w, respectively. The antioxidant assays showed that the bark possessed maximum antioxidant activity. The water extracts of S. glauca bark exhibited scavenging property (90%) with an IC50 value 39.63 μg/ml, and the least activity (56%) was observed in the methanol extracts of leaves with an IC50 value of 62.96 μg/ml of S. glauca. Conclusion: The study concluded that the water extract of the bark is a potent antioxidant compared to leaves and flowers. Further, in vivo studies are essential to enumerate its medicinal use and prove its efficacy in therapeutic applications.